2007
DOI: 10.3189/172756407782871251
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of glacier runoff to summer snowfall events

Abstract: In order to investigate the effect of changing precipitation type on glacier discharge due to air-temperature changes, the relation between summer snowfall and runoff is surveyed for the Vernagtbach basin, Austria, (2640–3630ma.s.l.; ~72% glaciated) for the period 1976–2005. Precipitation data were evaluated for each ablation season with respect to amount and type; the latter derived mainly from daily photographs of the catchment, but validated over 4 years with additional meteorological data. Winter snowfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In other mountain regions, such as the Vernagtbach basin in Austria, there are years when solid precipitation accounted for up to 70% of total precipitation during the ablation season. During the same period, there were up to 50 days with snowfall (Escher‐Vetter & Siebers, 2007). In the Hathataga catchment, solid precipitation accounted for 23% of total precipitation from May to September 2019 with 20 days of snowfall.…”
Section: Discussionmentioning
confidence: 99%
“…In other mountain regions, such as the Vernagtbach basin in Austria, there are years when solid precipitation accounted for up to 70% of total precipitation during the ablation season. During the same period, there were up to 50 days with snowfall (Escher‐Vetter & Siebers, 2007). In the Hathataga catchment, solid precipitation accounted for 23% of total precipitation from May to September 2019 with 20 days of snowfall.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature was 2 • C lower than in the 1940s and 2000s between March and September, and precipitation was higher, in particular during winter and spring. The solid fraction was also larger, principally in summer, with important effects on the summer balance of glaciers [53,67].…”
Section: Considerations On the Sensitivity Analysis Resultsmentioning
confidence: 99%
“…This entails crucial changes in albedo and therefore intensified ice melt and thinning of firn areas due to rising energy absorption at the glacier surface (Escher-Vetter, 2007;Braun et al, 2007). We interpret this as a regime shift as summer mass balances continue to be lower than before 1981 615 although (July) temperatures decrease again, with the exception of 1984, which was characterized by a relatively high number snowfall days during the ablation period (Escher-Vetter and Siebers, 2007).…”
mentioning
confidence: 88%
“…Escher-Vetter (2007 and Abermann et al (2009) have also shown that mass loss started in 1981 at both glaciers, resulting from negative 610 summer balances. With respect to the Vernagtferner, the drastically higher ablation area ratio of almost 80 % in 1982 as compared to around 25 % in the preceding years (Escher-Vetter and Siebers, 2007) indicates that large areas of the glacier became snow-free in 1982. This entails crucial changes in albedo and therefore intensified ice melt and thinning of firn areas due to rising energy absorption at the glacier surface (Escher-Vetter, 2007;Braun et al, 2007).…”
mentioning
confidence: 95%